Strategi Pembelajaran Aktif Learning Dalam Pembelajaran Bahasa Arab di Pondok Pesantren Darul Lughah Waddirasatil Islamiyah (DALWI) Pamekasan - Moh. Mofid (Universitas Yudharta Pasuruan, 2019)
Active learning is a learning process with the intent to empower students to actively learn. In this case the process of learning activities are dominated by students using the brain to find the concept and solve the problem that is being studied, in addition to preparing the mental and training physical skills. How to empower students not only by using a strategy or method of discourse, as long as it is used by teachers in the learning process. Teaching with a lecture means giving an information through hearing, which can only be digested in the brains of 20% students. Whereas the information students learned could be from the pottery (10%), Qiroah (30%), special (50%), Kalam (70%), doing and practicing (90%). This active learning strategy can not only be implemented in formal education only, education pesantren can apply several strategies such as in Arabic language learning in the islamic boarding school Darul Lughah Waddirasatil Islamiyah Pamekasan. This research is presented in a descriptive form with the intention to describe something that is happening in the field. His research approach was a qualitative approach. Data collection techniques use: observation, interviews and documentation. While the research object in one of the Arabic huts in the city of Pamekasan is the islamic boarding school Darul Lughah Waddirasatil Islamiyah Pamekasan which specifically study both active and passive Arabic language and Islamic sciences.